Developing intercultural communicative competence: An example of the New College English textbook series - Tamas Kiss (Universitas Katolik Indonesia Atma Jaya, 2017)
The development of intercultural communication has received renewed attention in the professional literature in the past decade. In response to changes brought about by a globalizing world and educational industry, our understanding of culture – and its role in language teaching - has changed. This is clearly indicated by the emerging 21st century educational frameworks that put inter- and cross-cultural skills as one of the core competencies for students to be successful in a rapidly changing world. Research on language teaching materials has found that there has been a shift in cultural representations, moving from mono-cultural portrays to more dynamic, inter-cultural, even hybrid cultural depictions. Yet, two areas need further consideration: a) While the above might be true for materials developed for international markets, how is culture represented in locally produced English language textbooks? b) What tasks are used in the materials to develop the skills, attitudes, and knowledge needed for successful intercultural communication? This paper set out to examine a widely used and locally published English language textbook series by using Byram’s (1997a) framework and found that although the material has a potential to develop intercultural competence, it does not provide tasks that would engage students in such learning.